Securing Water for Agriculture : A Guide to Investment Decisions - World Bank (Washington, DC, 2012)
How can the world grow more food, increase incomes, reduce poverty, and protect the environment with growing numbers of mouths to feed and increasingly constrained resources? A big part of the answer lies in better management of agricultural water. Agricultural water management (AWM) encompasses irrigation on both a large and small scale, drainage of irrigated and rain fed areas, watershed restoration, recycling of water, rainwater harvesting, and better in-field water management practices. There is considerable scope for improving returns on water from agricultural use. The key economic challenge is to set up an incentive framework that encourages efficient water use and profitable high value agriculture. Evidence indicates that such a framework improves efficiency and accountability, raises productivity, and promotes sustainable and environmentally responsible resource use. At the same time, irrigation schemes pose a financial challenge: to recover costs at a rate sufficient to finance services to farmers. The broad challenge is to encourage both large- and small-scale private investment.